(untitled) - Franzini, Louis R. (New York, 1995)
All of the stories contained in Eccentric and Bizarre Behaviors are based on actual case studies. Throughout, Drs. Franzini and Grossberg discuss, in terms that general readers can understand, both the known and conjectural causes for the strange disorders they describe. And, in many cases, they recount the stirring details of how patients were ultimately rescued from the eccentric and bizarre patterns of behavior in which they had become imprisoned.
Keywords: Psychology, pathological,Psychology, pathological,Tâm lý học, bệnh lý; Case studies,Nghiên cứu